Des choses de la nature et de leurs droits. - Vanuxem, Sarah (éditions Quae, 2020)
The purpose of environmental law is to protect nature, to fight against pollution and nuisances, to improve the quality of life and public health. In light of recent legal innovations, the author examines the transformations that environmental law has brought to our civil law tradition. Starting from the hypothesis that it is possible, but also desirable, to view environmental law as something other than an instrument for the commodification of nature, the author revisits contemporary environmental law by drawing inspiration from certain principles of medieval law. She asks to what extent we have not already broken with the modern Western conception, and begun to build a system articulated around the values of ecological service, ecological solidarity, or reparation of ecological damage.
Keywords: Environment law.; Environmental law.; Environmental protection.; Reparation (Criminal justice); ecology,environment